PENGEMBANGAN INDIKATOR 4C’s YANG SELARAS DENGAN KURIKULUM 2013 SMA KELAS X PADA MATERI TRIGONOMETRI - Yuniar, Sita Nastiti; Sunardi, Sunardi; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research aims to produce valid development of 4C’s indicators which are in accordance to the curriculum of 2013 for tenth grade of Senior High School/MA on trigonometry subject. The type of research used is a modified Plomp’s development model consisting of 4 phases: preliminary investigation, design phase, realization/construction phase, and test, evaluation and revision phase. The development in this research is 4C's indicators which are in accordance to the curriculum of 2013 for tenth grade of Senior High School/MA on trigonometry subject consisting of 12 basic competencies. Instrument which was used is validation sheet of 4c’s indicators that are in accordance to the curriculum of 2013. The results of this development are validated by 5 validators. The results of the recapitulation showed that the total number of 4C's indicators developed amounted to 97. The largest percentage lies in critical thinking ability indicators which is equal to 41.23%. Furthermore, the percentage of creative ability indicators is equal to 16,49%, percentage of collaboration ability indicators is equal to 16,49%, and percentage of communication ability indicators is equal to 25,77%. The results of the development of 4C's indicators have a coefficient of 3.93 which is categorized as good. So, the development of 4C's indicators that are in accordance to the curriculum of 2013 for tenth grade of Senior High School/MA on trigonometry subject has met the criteria of validity. Keyword: Plomp’s development, 4C's skill, Curriculum 2013